Research trends in leadership communication using Motivating Language Theory: a systematic literature review - Rachmani, Ira Dwi; Sarwoprasodjo, Sarwititi; Muljono, Pudji; Pertamasari, Riko Bintari (Jurnal Studi Komunikasi, 2025)
Abstract The Motivating Language Theory (MLT) offers a robust framework for analysing how strategic verbal communication can motivate individuals and enhance organisational performance. This study answers the research questions of identifying the profile and characteristics of the MLT research literature, examining the theories and variables used in MLT studies in organisational communication, and mapping existing research to highlight gaps and suggest future research directions. Using a systematic literature review guided by the PRISMA protocol, 77 articles from the Scopus database were analysed with Microsoft Excel and VOS viewer. Findings reveal a growing interest in MLT, particularly in the private sector, with most studies employing quantitative methods. The review highlights diverse theoretical integrations, identifies research gaps, and recommends future studies in cross-cultural contexts, high-pressure industries, and remote or hybrid work settings to advance both theoretical and practical insights in organisational communication.